Assessing the quality of research examining change in children’s mental health in the context of COVID-19 - Vaillancourt, Tracy; Brittain, Heather; Krygsman, Amanda; Davis, Adam; Farrell, Ann; Desmarais, Riley; Hammill, Charlotte; Karasz, Sarah; Morgan, Rachael; Ritchie, Annie; et al. (University of Ottawa Journal of Medicine, 2021)
In their policy brief on the impact of COVID-19 on children and youth, the United Nations identified the need for “a rapid accumulation of data on the scale and nature of impacts among children.”1(p14) Although an important goal, this call to action defies how research typically unfolds. Science is a slow, methodical process that requires careful consideration of prior evidence, ethics, measurement, sampling, analysis, and implications, to name a few. Still, we appreciate the call to shift priorities and allocate resources to conduct research about this global event. The stakes are high and information is needed to guide us on how children and youth are faring during this unprecedented time. One problem is that sub-standard studies, often released as non-peer reviewed preprints, are being promoted on social media and in news outlets, and this attention can influence the public’s perception of risk, the credibility of scientists, and policy makers’ decisions related to funding and programming. Some scholars and medical professionals see preprints as a necessity during the pandemic to circumvent the lengthy review process and to arm professionals with the most up-to-date data.2 Others see this growing trend as facilitating the spread of misinformation because, unlike scientists who approach non-peer reviewed research with caution, popular news outlets and the public may take preprints at face value.3,4 Our goal is thus to remind readers of what constitutes good science in the field of child and youth mental health.